TECHNOLOGY FOR PRODUCING FUEL FROM OIL SLUDGE (Scientific journal of the Fergana State University, 2026)
Oil sludge formed in oil and gas production, transportation, and storage facilities contains significant amounts of hydrocarbons, water, and mineral impurities, which complicates its processing in conventional oil-refining units. The present study investigates the fractional composition and physicochemical properties of oil sludge accumulated at the “Shimoliy So‘x” underground gas storage facility. The sludge samples were separated into layers according to depth and analyzed through atmospheric distillation. Based on the obtained data, an innovative reactor design capable of processing highly contaminated oil sludge was developed. The reactor incorporates an economizer to improve thermal efficiency and facilitates easy removal of solid residues. Laboratory experiments confirmed the operability of the system, and the produced technological fuel was successfully tested in asphalt production. The proposed solution significantly reduces environmental emissions from sludge-storage ponds and decreases ecological payments for industrial enterprises.